Bridges of Vietnam : From the Journals of a U.S. Marine Intelligence Officer. - Jr, Fred L. Edwards (University of North Texas Press, 2001)
As an intelligence officer during the Vietnam War, Fred L. Edwards, Jr., was instructed to visit every major ground unit in the country to search for intelligence sources-long range patrols, boats, electronic surveillance, and agent operations. "Edwards found time to keep a journal, an extremely well-written, sharply observed report of his adventures. Along with contemporary postscripts and a helpful historical chronology, that journal is a significant improvement on most Vietnam memoirs. It is the record of a Marine's on-the-job education."--Proceedings.